The Relationship Between Fasting Duration and The Incidence of Post Operative Nausea and Vomiting in Spinal Anesthesia Patients - Husnul Khotimah Muliono, Siti; Susanto, Amin; Sebayang, Septian (Java Nursing Journal, 2024)
Background: Anesthesia, a critical pain management tool during surgeries and procedures, necessitates pre-operative fasting to mitigate the risk of post-operative nausea and vomiting (PONV). The fasting period restricts both solid and liquid intake. Purpose: This study aims to explore the correlation between fasting duration and the incidence of PONV in patients undergoing spinal anesthesia at Dr. Soedirman Regional Hospital, Kebumen. Method: Employing an analytical observational design with quantitative methods, this research included 70 participants selected through cross-sectional sampling. Data collection utilized the Rhodes Index of Nausea, Vomiting, and Retching (RINVR) scale for observation. Findings: The study revealed that the majority of respondents (54.3%) adhered to an adequate fasting duration of 6-8 hours. Among these, 89.5% (34 respondents) did not experience PONV. Conversely, an inadequate fasting period (>8 hours) was associated with a higher incidence of PONV, observed in 38.6% (27 respondents), while only 3.7% (1 respondent) did not experience PONV. The correlation analysis yielded a significant relationship with a coefficient of 0.502. Conclusion: There is a significant correlation between fasting duration and the incidence of PONV in patients receiving spinal anesthesia at Dr. Soedirman Regional Hospital, Kebumen. Adequate pre-operative fasting (6-8 hours) is associated with a lower incidence of PONV, emphasizing the importance of adherence to recommended fasting guidelines to minimize post-operative complications